Utilization of personal protective equipment and its key factors among WA oil factory workers in Debre Markos town, Ethiopia - Teym, Abraham; Zeleke, Tirsit Ketsela (Frontiers in Public Health, 2025)
BackgroundEdible oil manufacturing is a labor-intensive sector with significant technological demands, where employees face various occupational hazards. The use of personal protective equipment (PPE) is not only a legal obligation but also a key measure for safeguarding workers against job-related injuries and health risks. Despite these challenges, this industry often remains under-researched and overlooked.ObjectiveTo assess utilization of personal protective equipment and its key factors among workers in the WA edible oil factory in Debre Markos town, Ethiopia, in 2024.MethodsA cross-sectional study was conducted among employees of the WA Edible Oil Factory in Debre Markos. Using a simple random sampling method, 387 workers were selected to participate. Data were collected through an interviewer-administered structured questionnaire, focusing on the use of protective equipment, as well as socio-demographic, work-related, environmental, and organizational characteristics. The data were analyzed using SPSS version 26. Logistic regression analysis was employed to identify factors influencing the use of protective equipment, with the strength of associations expressed as odds ratios at a 95% confidence level.ResultsOut of the total workforce, 214 individuals (55.3%) reported using personal protective equipment while on duty. The study identified several significant factors influencing personal protective equipment utilization, including receiving safety training, having access to protective equipment, regular occupational health and safety inspections, the presence of workplace safety protocols, having three or more years of work experience, and abstaining from alcohol consumption and smoking.ConclusionThe utilization level of personal protective equipment among workers at the WA edible oil factory was found to be moderate when compared to findings from other developing countries. Key factors influencing personal protective equipment usage included access to safety training, availability of protective gear, workplace supervision, the presence of safety protocols, work experience, and lifestyle behaviors such as alcohol and tobacco use. To improve personal protective equipment utilization, it is recommended to strengthen workplace supervision, offer comprehensive safety training, and ensure the consistent availability of safety guidelines.